Exploring the nutritional composition, physicochemical properties, and biological characteristics of mature banana varieties (Musaceae) - Ngoc Duc Vu; Nguyen Trinh Thi Nhu Hang; Kieu Dang Quynh Mi; Nguyen Huu Thuan Anh; Binh An Pham (Food Chemistry: X)
Despite the global significance of bananas, detailed characterization of their nutritional, physicochemical, and bioactive properties remains limited, especially for rare or regionally cultivated varieties. This study profiles 13-banana cultivars from Vietnam to identify varietal differences and assess their potential in food applications, using a multi-dimensional framework including morphology, surface color, and texture. Physicochemical characteristics and proximate nutritional components were assessed using validated methodologies. Moreover, key bioactive compounds and antioxidant activities were quantified via spectrophotometric assays. Results revealed significant inter-cultivar variation across all analytical domains. Ta Qua exhibited the largest fruit morphology and the highest carbohydrate content (>40.29 g/100g), while Cha Bot demonstrated elevated concentrations of phenolic and flavonoid compounds, correlating with robust antioxidant activity (1.17–1.67 mgAA/gDW). Conversely, Sap Trang presented limited antioxidant capacity but was comparatively rich in protein (1.89 g/100g). The study highlights the importance of cultivar-specific profiling to support evidence-based selection for nutrition, breeding, and food development.